Pap tests for cervical cancer screening test and contraception: analysis of data from the CONSTANCES cohort study - Stéphanie Mignot; Virginie Ringa; Solène Vigoureux; Marie Zins; Henri Panjo; Pierre-Jean Saulnier; Xavier Fritel (BMC Cancer, 2019)
Abstract Background In France, a Pap test for cervical cancer screening is recommended every three years for all sexually active women aged 25 to 65 years. Modes of contraception (any or no contraception, with or without a visit to a physician, and with or without a gynecological examination) may influence adhesion to screening: women who use intrauterine device (IUD) should be more up to date with their cervical cancer screening more often than those using other means of contraception. Our objectives were to analyze the association between modes of contraception and Pap tests for screening. Methods This cross sectional study is based on the CONSTANCES cohort enabled us to include 16,764 women aged 25–50 years. The factors associated with adhesion to cervical cancer screening (defined by a report of a Pap test within the previous 3 years) was modeled by logistic regression. Missing data were imputed by using multiple imputations. The multivariate analyses were adjusted for sex life, social and demographic characteristics, and health status. Results Overall, 11.2% (1875) of the women reported that they were overdue for Pap test screening. In the multivariate analysis there was no significant difference between women using an IUD and those pills or implant of pap test overdue ORa:0.9 CI95% [0.8–1.1], ORa 1.3 CI95% [0.7–2.7] respectively. Women not using contraceptives and those using non-medical contraceptives (condoms, spermicides, etc.) were overdue more often ORa: 2.6 CI95% [2.2–3.0] and ORa: 1.8 CI95% [1.6–2.1] respectively than those using an IUD. Conclusion Women seeing medical professionals for contraception are more likely to have Pap tests.